Student almanac of Hispanic American history. - Media Projects Incorporated (Westport, Conn. : Greenwood Press, 2004)
Uses primary source documents, maps, charts, and statistics to trace the history and contributions of Hispanic Americans from their first travels across the Atlantic to the present day.
v. 1. From European contact to the U.S.-Mexican War, 1492-1848 -- v. 2. From the California Gold Rush to today, 1849-present.
"A Media Projects, Inc. Production"--T.p. verso.
Includes bibliographical references and indexes.
Keywords: Hispanic Americans -- History -- Miscellanea -- Juvenile literature; Hispanic Americans -- History -- Sources -- Juvenile literature; Almanacs, American -- Juvenile literature; Hispanic Americans -- History -- Miscellanea; Hispanic Americans -- History -- Sources